Side-by-side partially covered self-expandable metal stent placement for malignant hilar biliary obstruction - Katsuya Kitamura; Akira Yamamiya; Yu Ishii; Yuta Mitsui; Tomohiro Nomoto; Hitoshi Yoshida (Endoscopy International Open, 2017)
Background and study aims This study investigated the feasibility of side-by-side (SBS) partially covered self-expandable metal stent (PCSEMS) placement for unresectable malignant hilar biliary obstruction (MHBO). Patients and methods We retrospectively analyzed 33 patients from a single center who underwent endoscopic biliary drainage for unresectable MHBO from July 2013 to June 2015. In all patients with bilateral obstruction during complete bilateral intrahepatic cholangiograms, we performed endoscopic SBS placement of a 6-mm diameter PCSEMS using an 8-French delivery system. All patients underwent endoscopic sphincterotomy. Generally, patients with recurrent biliary obstruction (RBO) after stent placement underwent endoscopic reintervention. Our study outcomes included the technical and functional success rates, RBO rate, time to RBO (TRBO), reintervention rate, and incidence of adverse events. Results Seventeen patients with unresectable MHBO during complete bilateral intrahepatic cholangiograms underwent endoscopic SBS PCSEMS placement (median age, 78 years; men, 9). Lesions were Bismuth types II (n = 10), III (n = 1), and IV (n = 6), including 10 cholangiocarcinomas, 3 gallbladder cancers, and 4 metastatic cancers. In all patients, the PCSEMS was placed across the duodenal papilla. The technical and functional success rates were 100 % and 82 %, respectively. The median procedure time was 43 minutes (interquartile range [IQR]: 36 – 52 minutes). Twelve patients had RBO (71 %), including 9 stent occlusions due to sludge and 3 stent migrations. The median TRBO was 79 days (IQR: 58 – 156 days) during the follow-up period (median 192 days [IQR: 88 – 551 days]). The median TRBO of patients with Bismuth type II lesions was significantly longer than that of patients with Bismuth types III and IV lesions (87 days [IQR: 70 – 244 days] vs. 54 days [IQR: 35 – 100 days]; P  = 0.030). Thirteen patients (76 %) required endoscopic reintervention. Endoscopic stent removal was possible in 6 patients without tumor ingrowth into the uncovered distal part of the stent. One late adverse event (≥ 31 days) occurred (cholangitis). Conclusions Endoscopic SBS placement of a PCSEMS was feasible in patients with unresectable MHBO. Additionally, reinterventional stent removal was possible in the absence of tumor ingrowth.